2014
DOI: 10.1002/pros.22810
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride treatment alters tissue specific androgen receptor expression in prostate tissues

Abstract: BACKGROUND Normal and pathologic growth of the prostate is dependent on the synthesis of dihydrotestosterone (DHT) from testosterone by 5α-reductase. Finasteride is a selective inhibitor of 5α-reductase 2, one isozyme of 5α-reductase found in abundance in the human prostate. The objective of this study was to investigate the effects of finasteride on androgen receptor expression and tissue morphology in human benign prostatic hyperplasia specimens. METHODS Patients undergoing transurethral resection of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
(74 reference statements)
1
23
0
1
Order By: Relevance
“…These patients display a wide range of BPH related symptoms, making them good sources of transition zone (TZ) tissue with which to examine the genesis of BPH (Bauman et al, 2014a, Bauman et al, 2014b, Lin-Tsai et al, 2014, Ma et al, 2012, Nicholson et al, 2013). We typically collect 1–3 grams of TZ from these patients, and upon histological evaluation, approximately 50% of the tissues are viable, cancer-free specimens.…”
Section: Methodsmentioning
confidence: 99%
“…These patients display a wide range of BPH related symptoms, making them good sources of transition zone (TZ) tissue with which to examine the genesis of BPH (Bauman et al, 2014a, Bauman et al, 2014b, Lin-Tsai et al, 2014, Ma et al, 2012, Nicholson et al, 2013). We typically collect 1–3 grams of TZ from these patients, and upon histological evaluation, approximately 50% of the tissues are viable, cancer-free specimens.…”
Section: Methodsmentioning
confidence: 99%
“…The recent study of Wen et al [32] showed that androgen receptors located in the prostate stroma may take part in the etiology of BPH. The immunohistochemical analysis of androgen receptors in BPH patients treated with finasteride conducted by Bauman et al [33] suggests that this treatment may decrease the expression of this receptor in the prostate epithelium. Biolchi et al [34] analyzed genotypes and testosterone levels in a group of 126 patients, aged 40 to 60 years, whose prostate volumes exceeded 30 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was recommended that this drug should be used in the perioperative period. However, the effectiveness of finasteride in BPH treatment is associated with its inhibition of angiogenesis, and negative its effect on local anti-inflammatory agents [8,9]. However there are few reports on the impact of administration of finasteride in the perioperative period on the serum levels of inflammatory factors of patients.…”
Section: Introductionmentioning
confidence: 99%